Proyecto de inversión para la elaboración de un edulcorante natural hecho a base de stevia en la provincia de El Oro - Terán Elizalde, Eric Xavier (2010)
Stevia is plant, native to subtropical and tropical South America and Central America. The species Stevia rebaudiana Bertoni, commonly known as sweetleaf, or simply stevia, is widely grown for its sweet leaves. As a sugar substitute,to 300 times the sweetness of sugar, stevia has garnered attention with the rise in demand for lowcarbohydrate,. Medical research has also shown possible benefits of stevia in treating obesity and high blood pressure. Because stevia has a negligible effect on blood glucose, it is attractive as a natural sweetener to people controlled diets. However, health and political controversies have limited stevia's availability in many countries; Stevia is widely used as a sweetener in Japan, and it is now available in Europe.